Career paths in human-animal interaction for social and behavioral scientists - Kogan, Lori; Erdman, Phyllis, 1949- (New York, NY : Routledge, 2021)
"Career Paths in Human-Animal Interaction for Social and Behavioral Scientists is an essential text for students and professionals wanting to pursue a career in Human-Animal Interaction (HAI). It is exclusively designed to navigate this field and provide information on the best education, training, and background one might need to incorporate HAI into a successful career. Kogan and Erdman bring together a diverse range of insights from HAI social scientists who have secured or created their HAI job. The book highlights six categories of work settings: academia, private practice, corporations/for profit companies, non-profit organizations, government, and other positions, to show the growing number of opportunities to blend social science interests with the desire to incorporate HAI into their careers. The chapters reflect the various career paths and educational backgrounds of a wide variety of professionals who have found their career choice in human-animal interaction. The book clearly outlines the career paths available to social science students and professionals, from careers connected to human services of psychology, therapy, social work and journalism to research or other scholarship"--
OCLC-licensed vendor bibliographic record.
Keywords: Social scientists -- Vocational guidance; Human-animal relationships; PSYCHOLOGY / General